Antihypertensive drugs in pregnancy. Issue 1 (1st March 2013) - Gasnier, Rose; Valério, Edimárlei Gonsales; Ramos, José Geraldo Lopes
Abstract : Chronic hypertension complicates 3%-5% of pregnancies and gestational hypertension occurs in 6% of pregnancies. Preeclampsia complicates 25% of the pregnancies with chronic hypertension, and approximately 15%-45% of the patients with gestational hypertension will develop preeclampsia, a dangerous condition that harms the maternal and fetal safety. Antihypertensive medication is used to treat severe hypertension to prevent serious maternal and fetal complications, but there is no consensus on when and how to treat mild-to-moderate hypertension in pregnancy. This article reviews the usage, effect and safety of first, second and third line antihypertensive drugs for mild-to-moderate hypertension in pregnancy.